Effectiveness of Differentiated Explorative Flipbooks to Improve The Learning Independence of Junior High School Student - Ni Putu Eva Yuliawati; Arimbawa, Gusti Putu Arya; Windhu, I Putu Tresna; Agustini, Ketut; Sudatha, I Gde Wawan (Jurnal Nasional Pendidikan Teknik Informatika: JANAPATI, 2025)
This research was conducted to overcome the low level of learning independence of students as indicated by dependent behavior among students at the junior high school level. The ADDIE development model was chosen as a model for developing and implementing learning tools to overcome the problem of student learning independence. Data was collected through non-tests using the Learning Object Review Instrument, User Experience Questionnaire and questionnaires to measure students' learning independence. Data analysis was carried out using percentages and n-gain scores. The result of this research was the creation of a product called Mekdi with an average gain score increase of 0.39 which is in the medium category. There are various elements that support the learning process and increase students' learning independence in this media including flipbook elements, GeoGebra exploration, diagnostic assessments, collaboration spaces, and ice breaking activity.